Media, Islam, dan Politik Identitas dalam “Bulan Terbelah di Langit Amerika” - Aziz, Abdul Muhaiminul; Mutqiyyah, Rizqi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
Western media is considered to have an important role war in constructing a negative image of Islam throughout the world, especially after the 9/11 WTC attacks. It inspired the emergence of various popular cultural products, especially in several Muslim-populated countries, which carried out a counter-culture to this reality. This study discusses how the construction of Islam within Western media in the novel Bulan Terbelah Di Langit Amerika. This research used a qualitative method utilising a media text analysis approach. The results showed that the media played an important role in constructing the identity of Islam, as the world enemy, was a media marketing strategy to increase product circulation. This negative view of Islam may be due to the absence of comprehensive information about Islam.